2005
DOI: 10.1111/j.0008-3658.2005.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Rural population change in Nova Scotia, 1991–2001: bivariate and multivariate analysis of key drivers

Abstract: Depopulation is a major demographic and economic issue in Nova Scotia, as it is in many of Canada's hinterland areas. Indian Reserves excepted, two‐thirds of rural census subdivisions declined in population between 1991 and 2001, and this decline has serious economic and social consequences. By contrast, a small minority of seemingly ‘rural’ areas is experiencing excessive population growth through exurbanisation. This article combines map and graph analysis with simple regression and multivariate techniques t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…These were: population growth; median household income growth; change in the labour force participation rate and; labour force growth. These variables, while being valuable measures of socio‐economic performance in their own right, have also been identified as closely tied to a range of other socio‐economic conditions, such as poverty, employment opportunities, and economic activity (Mencken and Singelman, 1998; Dissart, 2003; Feser and Sweeney, 2003; Millward, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These were: population growth; median household income growth; change in the labour force participation rate and; labour force growth. These variables, while being valuable measures of socio‐economic performance in their own right, have also been identified as closely tied to a range of other socio‐economic conditions, such as poverty, employment opportunities, and economic activity (Mencken and Singelman, 1998; Dissart, 2003; Feser and Sweeney, 2003; Millward, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…We are, however, cautious about the issue of both causality and the influence of other variables. In terms of the latter, the literature suggests that processes other than diversity can affect all of our measures of socio‐economic performance (Mencken and Singelman, 1998; Millward, 2005). While it would also have been useful to include other variables, such as population size or dependence on agriculture and mining, given the sample size this would have resulted in an excessive number of variables in the regression model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature related to the measurement, impact and importance of population density in the rural settlement of developed countries has been reviewed by Smailes, Argent, and Griffin (2002). More recently, Muilu and Rusanen (2004) traced the links between density and changes in the sectoral composition of Finland's rural workforce; Millward (2005) found a relationship between rural density and the rate of population change in Nova Scotia; Argent, Smailes, and Griffin (2006) investigated factors that generate variation in rural density; Adolphson (2010), following others, developed a kernel density surface to examine the relation between density and functional complexity in a Swedish peri‐metropolitan setting; Schuurman, Bérubé, and Crooks (2010) found that kernel density was not a satisfactory measure of accessibility to primary health care; while a tendency to conflate density and remoteness measures (Zhao and Guthridge 2008) has been noted by Holmes (2009).…”
mentioning
confidence: 99%
“…Some authors have also mentioned the lack of educational opportunities and the need to access tertiary education as causal factors (Alston, 2004; Henkel, 1994; Holmes et al, 2005; Stockdale, 2002) as many young people in Australian small towns must relocate to access higher education. Among the reasons identified for out-migration are employment (Millward, 2005), declining employment in agriculture and other resource-based industries (McGranahan and Beale, 2002), and viability of job opportunities (Muilu and Rusanen, 2003). Expected income (Todaro, 1969) and household income (Millward, 2005) have also been identified.…”
Section: Introductionmentioning
confidence: 99%